2017
DOI: 10.1111/hae.13368
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and clinical features associated with the IPSG MRI tibiotalar and subtalar joint scores in children, adolescents and young adults with haemophilia

Abstract: Objectives:To assess the reliability of the IPSG MRI scale for tibiotalar (TTJ) and subtalar joint (STJ) changes in young haemophilic patients, correlating MRI findings with functional scores and 3D-rearfoot kinematics.Methods: A total of 37 haemophilic patients underwent bilateral MRI of the footankle, clinical evaluation and quantitative assessment of their 3D-rearfoot kinematics during walking. TTJ and STJ soft tissues were assessed twice along with osteochondral changes by two radiologists using the IPSG M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…An association between total IPSG‐MRI scores and both clinical gait features was found. Brunel et al previously reported weak associations between this IPSG‐MRI score and kinematic gait features in haemophilic children with no to moderate ankle joint damage. These authors did however not find any associations between synovial hypertrophy findings and gait features as synovial hypertrophy lesions were not common in their study population, contrarily to the current study.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…An association between total IPSG‐MRI scores and both clinical gait features was found. Brunel et al previously reported weak associations between this IPSG‐MRI score and kinematic gait features in haemophilic children with no to moderate ankle joint damage. These authors did however not find any associations between synovial hypertrophy findings and gait features as synovial hypertrophy lesions were not common in their study population, contrarily to the current study.…”
Section: Discussionsupporting
confidence: 46%
“…The main findings of this study seem to substantiate our initial hypothesis as PwH with severely damaged ankle joints generate and absorb less ankle joint power, which is correlated with a lowered tolerance towards ankle joint stress during walking. Potential reasons for the found correlations might arise from ankle pain during walking, limited mobility and stiffness and calf muscle atrophy and/or weakness due to muscle bleedings or disuse in patients with severe haemophilia. These functional consequences in the ankle joint often lead to antalgic walking patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Joint structural integrity in these studies was assessed with disease‐specific clinical scores (eg HJHS, World Federation of Haemophilia clinical score). However, these scores show good sensitivity with respect to the detection of early stages of ankle arthropathy but not for other major foot joints such as the subtalar joint . Thus, the relationship between HA and postural control remains poorly studied.…”
Section: Introductionmentioning
confidence: 99%